Legal Consequences of Binding the Sale and Purchase of Land Rights Under Hands That Have Been Warned by a Notary - Prahmono, Siget (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2024)
The researcher conducted this research with the intention of knowing and analyzing the legal status of PPJB for private land rights that have been Waarmerking and also to find out and analyze whether a PPJB for private land rights that has been Waarmerking must make a Deed of Sale and Purchase. In this study, a sociological legal approach will be used and primary data will be used as the main data, namely the results of interviews conducted with Mrs. Arini Sutanti, S.H., M.Kn. She is one of the Notaries in Temanggung Regency and is also supported by secondary data from a number of sources which are then analyzed and processed using qualitative methods in order to obtain a conclusion. The results of the study show that the sale and purchase agreement for land rights carried out privately which was then carried out by Waarmerking efforts by the Notary does not affect the authenticity of the contents or signatures contained in the deed, the role of Waarmerking is only limited to entering it in the Notary's book as an archive if at some point the agreement letter is lost or damaged, so that all parties who bind themselves do not have to re-make the agreement letter. This means that the evidentiary power and status of the Waarmerking itself can be interpreted as if the Notary has no responsibility for the contents and signatures contained therein, so the related parties will only have responsibility for the contents and signatures contained in the letter.